Combination effects of salts and cold storage on the formation of protein-bound Nɛ-(carboxymethyl)lysine and Nɛ-(carboxyethyl)lysine in raw and subsequently commercially sterilized ground pork. (30th October 2018) - Niu, Lihong; Sun, Xiaohua; Tang, Juming; Wang, Jianhui; Wang, Jing; Rasco, Barbara A.; Lai, Keqiang; Fan, Yuxia; Huang, Yiqun
Highlights: Carboxymethyllysine (CML) and carboxyethyllysine (CEL) in ground pork were measured. Salts and storage (0 °C, ≤8 days) had little effect on CML or CEL level in raw pork. Raw pork stored for 8 days caused 33–83% increase of CML or CEL in sterile products. NaCl (1.5–5%) in pork promoted heat-induced CML formation. NaNO2 (50–150 ppm) could inhibit heat-induced CML and CEL formation. Abstract: The effects of cold storage (0 °C, 0–8 days) and salts (NaCl, 0.5–5%; NaNO2, 50–150 mg/kg) on the formation of protein-bound N ɛ -(carboxymethyl)lysine (CML) and N ɛ -(carboxyethyl)lysine (CEL) in raw and subsequently commercially sterilized (121 °C, 10 min) pork were investigated. Based upon two-factor analysis of variance (α = 0.05), there was no significant interaction effect between salts and storage time on the levels of CML and CEL in raw or sterile pork; salts and storage time did not significantly affect the amounts of CML and CEL in raw pork. However, in sterile pork, 1.5–5% NaCl treatments led to an average of 7.5–52.6% increase in CML, while NaNO2 resulted in 25.4–37.1% and 21.4–23.4% reduction in CML and CEL, respectively; raw pork stored for 8 days led to 82.5% increase of CML and 32.6% increase of CEL in the sterile products ( n  = 30), as compared to those without cold storage.